1991
DOI: 10.2134/agronj1991.00021962008300010025x
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Composition of Tropical Grass‐Legume Pastures Estimated with Near‐Infrared Reflectance Spectroscopy

Abstract: Quantifying pasture composition requires either laborious or subjective approaches. Evaluations of near‐infrared reflectance spectroscopy (NIRS) to determine botanical composition of mixed pasture swards have shown potential. In this study, characterization of botanical composition of pastures comprised primarily of bahiagrass (Paspalum notatum Flugge), aeschynomene (Aeschynomene americana L.) and phasey bean [Macroptilium lathyriodes (L.) Urb.] by NIRS was evaluated. Three approaches (hand‐composited samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
4
25
0
Order By: Relevance
“…On fodder mixtures, two different methods have been applied to provide the pure material for calibration series, so called “artificial” and “real” samples (Cougnon et al, 2013). It has been claimed that calibrations based on “artificial” samples, which are attained from pure stands (Coleman et al, 1985; Petersen et al, 1987), have good calibration statistics but fail to predict real validation samples while “real” samples, obtained by hand sorting of species mixtures (Shaffer et al, 1990; Wachendorf et al, 1999), reflect the environmental and thus spectral variation to a greater extent (Pitman et al, 1991; Cougnon et al, 2013). Studying roots, Roumet et al (2006) used both “artificial” and “real” samples, originating from both natural and environmentally controlled conditions, and found that the predictive equations for calibration were robust.…”
Section: Total and Taxa-specific Root Biomass Quantificationmentioning
confidence: 99%
“…On fodder mixtures, two different methods have been applied to provide the pure material for calibration series, so called “artificial” and “real” samples (Cougnon et al, 2013). It has been claimed that calibrations based on “artificial” samples, which are attained from pure stands (Coleman et al, 1985; Petersen et al, 1987), have good calibration statistics but fail to predict real validation samples while “real” samples, obtained by hand sorting of species mixtures (Shaffer et al, 1990; Wachendorf et al, 1999), reflect the environmental and thus spectral variation to a greater extent (Pitman et al, 1991; Cougnon et al, 2013). Studying roots, Roumet et al (2006) used both “artificial” and “real” samples, originating from both natural and environmentally controlled conditions, and found that the predictive equations for calibration were robust.…”
Section: Total and Taxa-specific Root Biomass Quantificationmentioning
confidence: 99%
“…Hand sorting is slow and laborious and although visual estimation is rapid, there may be many unquanti®able errors (Coleman et al 1985). Shenk et al (1979) originally showed that NIRS could be used to determine the proportion of legumes in legume-grass mixtures to an accuracy of about 10% and several studies have attempted to expand this concept to more complex pastures (e.g., Coleman et al 1990;Pitman et al 1991;Atkinson et al 1996). Arti®cial mixtures of Fig.…”
Section: Resolution Of Complex Mixturesmentioning
confidence: 99%
“…Near infrared reflectance spectroscopy (NIRS) is a rapid non-destructive technique with the capacity to distinguish and quantify botanical composition in mixtures (Locher et al 2005a;Pitman et al 1991;Wachendorf et al 1999). The fact that near-infrared radiation is absorbed mainly by C-H, N-H and O-H bonds, of which organic compounds are composed, makes it particularly suitable to determine the composition of organic mixtures (Foley et al 1998;Richardson and Reeves 2005).…”
Section: Introductionmentioning
confidence: 99%